Formulasi Patty Burger Non Daging Berbasis Jamur Tiram dan Batang Jamur Shitake dengan Tepung Non Gluten - Binardo Adi Seno Mawarno Mawarno; Made Darawati Darawati (Ma'soem University, 2026)
The high content of saturated fat and cholesterol is the reason for reducing the consumption of meat products and their derivatives. This study aims to formulate non-meat burger patty products using oyster mushrooms and shitake mushroom stems with three types of non-gluten flour as fillers, namely mocaf flour, tapioca flour and sago flour. The study used a Completely Randomized Design (type of non-gluten flour) with three replications and data analysis using One Way Anova with Duncan's differentiator test and Non Parametric Kruskal Wallis with Man Whitney Test. The quality tested included physical properties, namely cooking loss, water binding capacity and texture profile (hardness, gumminess, and springiness) as well as sensory properties with parameters of taste, aroma, texture and overall acceptance. The test results showed that the patty using tapioca flour had the smallest cooking loss and was significantly different between treatments. This is in line with the ability to bind water by starch granules contained in flour. Texture profile analysis resulted in the highest hardness value in mocaf flour patty, the highest gumminess in tapioca flour patty and springiness in sago flour patty. Sensory analysis based on all parameters showed that the patty with sago flour filling material was most preferred by 30 semi trained panelists. The addition of different types of non-gluten flour significantly affects the physical and sensory quality of the mushroom patty produced.